Encapsulation of Vitamins E and C in Whey Protein Concentrate-Chitosan Emulation: Physicochemical Properties - Mojtahedi, Pooneh; Mortazavian, Sayed Amir Mohammad; Varidi, Mehdi (Management Strategies and Engineering Sciences, 2023)
This study investigated the use of different ratios of whey protein concentrate (WPC) and chitosan (Cs) in encapsulating vitamins C and E. The aim of this research is the stability of vitamins C and E in environmental conditions. In this study, experimentally, the effect of different amounts of WPC and Cs on the chemical and physical properties of samples containing vitamin C and E is evaluated. The chemical and physical structures of the emulsions including (apparent viscosity, zeta potential, particle size, emulsion stability at pH 4.3 and 6.3 and the encapsulation efficiency of vitamins C and E) were investigated. The data was analyzed using Design Expert software. The main finding this study, the particle size, zeta potential, viscosity, emulsion stability in pH 4.3 and 6.3, and encapsulation efficiency of vitamins E and C varied from 255 to 595 nm, +20.11 to 31.77 mV, and 28.45 to 45.67 cP, 90 to 100% and 60 to 90%, and 93.83 to 93.36% and 93.60 to 77.33% respectively(p<0.05). In general, based on the results obtained from the response level, treatment 9 (WPC: Cs, 2: 0.25) at pH 4.3 had the lowest viscosity, particle size, and the highest particle size and encapsulation efficiency.